봉선화 전초의 메탄올 추출물이 신경세포에서 아밀로이드 전구단백질의 대사에 미치는 영향 - 조윤정(Yoon Jeong Jo); 임재윤(Jae Yoon Leem) (생약학회지, 2015)
One of the most common forms of dementia, Alzheimer's disease (AD) is a progressive neurodegenerative disorder symptomatically characterized by impairment in memory and cognitive abilities. AD is characterized pathologically by the presence of intracellular neurofibrillary tangles and deposition of ${β}$-amyloid ($Aβ$) peptides, believed to be neurotoxic and now is also considered to have a role on the mechanism of memory dysfunction. In this study, we tested that MeOH extract of Impatiens balsamina L. (IBM) affects on the processing of APP from the APPswe over-expressing Neuro2a cell line. We found that IBM increased over 2 folds of the $sAPPα$ secretion level, a main metabolite of ${α}$-secretase. We shown that IBM reduced the secretion level of $A{β}42$ and $A{β}40$ without cytotoxicity. BACE (${β}$-site APP cleaving enzyme) FRET assay shown that BACE activity was specifically decreased in the presence of IBM. We suggest that Impatiens balsamina L. may be an useful source to develop a herbal medicine of BACE inhibitor for Alzheimer's disease.